Analisis Pengaruh Sudut Kemiringan Solar Panel (Photovoltaic) Monocrystalline 50 Wp Terhadap Optimalisasi Output Daya - Wijayanti Sekarningrum, Wijayanti Sekarningrum (ENERGI & KELISTRIKAN, 2024)
Solar energy is converted into electrical energy through photovoltaic technology. Solar Power Plants are renewable energy sources that convert solar energy into electrical energy. To determine the optimal tilt angle or position for achieving optimal, effective, and efficient power output, voltage, and current, this study will discuss the influence of the tilt angle of solar panels on power output optimization. The research employs two different types of solar panels. The first solar panel has a fixed angle of 90°, while the second solar panel can adjust its angle between 0° and 180°. The tilt angle of the solar panels affects the generated power output, voltage, and current. The optimal angle occurs during the time range from 9:30 am to 1:00 pm (WIB), with the solar panel's tilt angle ranging from 57° to 99°. Solar panels capable of adapting their position to the movement of the sun are more effective in producing optimal power compared to fixed-angle panels. The temperature of the solar panels also affects the output voltage. The intensity of sunlight and changes in the tilt angle of the solar panels also influence the resulting electrical output.